The effect of painting parameters on the mechanical properties of injection-molded abs polymer for engineering purpose - Muhammad Izrul Fahmi Mohamed Rusli, 1994- 611619 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017